(untitled) (INNOTEC, 2017)
Eutrophication represents one of the main problems concerning continental aquatic ecosystems. An usual and undesired consequence of eutrophication is the occurrence of algal and cyanobacterial blooms, which hinders the proper functioning of these ecosystems and affects the services that they provide. Therefore, it is important to gain knowledge on the system’s functioning with the purpose to anticipate the temporal evolution of phytoplankton dynamics and their effects in the water quality. A key requirement is to generate monitoring strategies, which, in turn, may provide relevant information in decision-making processes regarding a variety of problems at different spatial-temporal scales. In this regard, this study intends to contribute to the systematization of available information that results from the monitoring and analyses of the processes underlying phytoplankton dynamics in Sauce Lake (Maldonado, Uruguay). Relevant progress, problems and challenges are identified and discussed. Finally, we highlight the importance of the integration of the information and the analyses generated by different institutions as well as the need to maintain these practices over time.